1998
DOI: 10.1074/jbc.273.15.8897
|View full text |Cite
|
Sign up to set email alerts
|

Degradation versus Aggregation of Misfolded Maltose-binding Protein in the Periplasm of Escherichia coli

Abstract: The periplasmic fates of misfolded MalE31, a defective folding mutant of the maltose-binding protein, were determined by manipulating two cellular activities affecting the protein folding pathway in host cells: (i) the malEp promoter activity, which is controlled by the transcriptional activator MalT, and (ii) the DegP and Protease III periplasmic proteolytic activity. At a low level of expression, the degradation of misfolded MalE31 was partially impaired in cells lacking DegP or Protease III. At a high level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 30 publications
(43 reference statements)
6
50
0
Order By: Relevance
“…Residual activation of s E may be the result of the production s E activation by C-source shifts of MalE, the extracytoplasmic maltose-binding protein/ receptor required for maltose utilization, as well as other maltodextrin-utilization proteins that are also expressed under these conditions (Hall et al, 1997). A previous study in E. coli found that at lower levels of expression a foldingdefective MalE protein is degraded by DegP or Protease III (Betton et al, 1998), supporting this idea. Unfortunately, knocking-out a required utilization component, such as MalE, would prevent growth on the C-source, and would again mimic C-starvation.…”
Section: Results and Disccusionsupporting
confidence: 62%
“…Residual activation of s E may be the result of the production s E activation by C-source shifts of MalE, the extracytoplasmic maltose-binding protein/ receptor required for maltose utilization, as well as other maltodextrin-utilization proteins that are also expressed under these conditions (Hall et al, 1997). A previous study in E. coli found that at lower levels of expression a foldingdefective MalE protein is degraded by DegP or Protease III (Betton et al, 1998), supporting this idea. Unfortunately, knocking-out a required utilization component, such as MalE, would prevent growth on the C-source, and would again mimic C-starvation.…”
Section: Results and Disccusionsupporting
confidence: 62%
“…The physiological role of Protease III is not known (Dykstra & Kushner, 1985;Swamy & Goldberg, 1982). It is thought that Protease III is involved in the turnover of proteins in the periplasmic space (Baneyx & Georgiou, 1991;Betton et al, 1998;Cornista et al, 2004). Thus, increased levels of Protease III may be needed after envelope stress.…”
Section: Members Of the S E Regulon Specific For S Typhimuriummentioning
confidence: 99%
“…coli K12 strains pop6590 and pop6499, which are both derivatives of MC4100 (Betton et al, 1998), were used as host strain for phenotype characterizations and protein production, respectively. Both strains carry the nonpolar deletion of the chromosomal malE gene, AmalE444 (Shuman, 1982), and pop6499 harbors the malTC' allele, which confers constitutive and high-level expression on the maltose operons (Debarbouille et al, 1978).…”
Section: Bacterial Struins and Plasmidsmentioning
confidence: 99%